Personalized exercise prescription in the prevention and treatment of arterial hypertension: a Consensus Document from the European Association of Preventive Cardiology (EAPC) and the ESC Council on Hypertension - Hanssen, H; Boardman, H; Deiseroth, A; Moholdt, T; Simonenko, M; Kränkel, N; Niebauer, J; Tiberi, M; Abreu, A; Solberg, EE; Pescatello, L; Brguljan, J; et al. (Oxford University Press, 2021)
Treatment of hypertension and its complications remains a major ongoing health care challenge. Around 25% of heart attacks in Europe are already attributed to hypertension and by 2025 up to 60% of the population will have hypertension. Physical inactivity has contributed to the rising prevalence of hypertension, but patients who exercise or engage in physical activity reduce their risk of stroke, myocardial infarction, and cardiovascular mortality. Hence, current international guidelines on cardiovascular disease prevention provide generic advice to increase aerobic activity, but physiological responses differ with blood pressure (BP) level, and greater reductions in BP across a population may be achievable with more personalized advice. We performed a systematic review of meta-analyses to determine whether there was sufficient evidence for a scientific Consensus Document reporting how exercise prescription could be personalized for BP control. The document discusses the findings of 34 meta-analyses on BP-lowering effects of aerobic endurance training, dynamic resistance training as well as isometric resistance training in patients with hypertension, high-normal, and individuals with normal BP. As a main finding, there was sufficient evidence from the meta-review, based on the estimated range of exercise-induced BP reduction, the number of randomized controlled trials, and the quality score, to propose that type of exercise can be prescribed according to initial BP level, although considerable research gaps remain. Therefore, this evidence-based Consensus Document proposes further work to encourage and develop more frequent use of personalized exercise prescription to optimize lifestyle interventions for the prevention and treatment of hypertension.